Shifting white SADF veteran identities from apartheid to contemporary South Africa - Weich, Francois (Rhodes University, Faculty of Humanities, Department of History, 2019)
The ideologies and structures of the apartheid state have received extensive academic attention, but the legacies of the militarisation of white South African men "“ a group that exists at a unique intersection of apartheid privilege and exploitation "“ have not been sufficiently addressed. Even as beneficiaries of apartheid, white men were militarised through structures of coercion and the mobilisation of identity constructions that resulted in the widespread submission to conscription and support for apartheid militarism. This thesis explores the relationship between those militarised identities and the historical processes of apartheid through a consideration of a broad range of white SADF veteran narratives from the Missing Voices Oral History Project archive. This consideration of the role of identity mobilisation in apartheid can shed light on the effect of historical processes of militarisation on white men in South Africa, as well as address the persistence of values and behaviours that may present barriers to the social transformation of South Africa towards a true constitutional democracy. The thesis explores identity in SADF veteran narratives through the application of social constructionism in order to determine the effect of coercive structures and identity mobilisation on individuals, and to gauge the persistence militarised identities after the social and political structures underpinning them had become defunct. The identity content of the narratives is contextualised in relation to structures of coercion employed by the apartheid state and the SADF alongside a consideration of the effect of political transition on veterans. The legacy of the historical environment and the impact of political transition on SADF veterans' constructed identities is investigated in relation to these veterans' own visions of their roles in post-apartheid South Africa. Therefore, this thesis endeavours to contribute to the expansion of the field of historical and identity study by considering the construction and renegotiation of military identities that maintained, benefited from, and were exploited by the apartheid state.
Keywords: South Africa -- History -- 1961-1994; Angola -- History -- South African Incursions, 1978-1990 -- Veterans; South Africa -- History, Military -- 1961-; Veterans -- South Africa -- Personal narratives; South Africa -- Armed forces; South Africa -- Politics and government -- 1961-1978; South Africa -- Politics and government -- 1978-1989; South Africa. South African Defence Force